A Takeover Case from Turkey's Privatization Affords of the State Owned Enterprises: Two-Step Leveraged Buyout Transaction - Recep Pekdemir; Ayca Zeynep Suer; Melis Ercan (Journal of Accounting and Management Information Systems (JAMIS), 2013)
This study aims to develop a real business life case on the two-step leveraged buyout transaction. Also, it is to share the case with the audience that might be globally related since the financial system has been global. And, consequently the language of financial reporting has been becoming uniquely global, too. In emerging economies, leveraged buyout transactions might be interesting for some stakeholders. In Turkey, one of the big corporate restructuring projects was to sell the majority shares of the Petrol Ofisi (The PO) that has been the leading oil distribution company. The PO privatization project and its consequences were gathered to develop the case. Since the PO was not only state-owned company during the privatization process, 7 % of the shares of the PO were publicly held in the Istanbul Stock Exchange (ISE). In the first step, a shell company acquired the PO, in the second step; the shell company and the PO (subsidiary company) were merged in the shell company. After the merging process, the name of the company stated as the PO again since it has had a good reputation in the local market. The company's story which is discussed in this study certainly does not resemble a typical privatization or a common merging transaction.
Keywords: M41; G34; G38; 650; Takeover; leveraged buyout; privatization; financial reporting